The Influence of Brand Collaboration and Price Image On Purchase Intention Mediated By Design (An Empirical Study of The Passion Jewelry Consumers In Jakarta) - Adella Puspa Amiata; Liem Bambang Sugiyanto (Asian Journal of Social and Humanities, 2024)
The objective of this research is to investigate the impact of brand collaboration and price image on purchase intention, as well as to examine the role of design as a mediating variable among consumers of the Passion Jewelry brand in Jakarta. Data for this study were collected through both online and offline methods, involving 185 respondents who are diamond jewelry consumers and owners in Jakarta. This research adopts a quantitative approach utilizing structural equation modeling, processed using the AMOS 24 software. The findings of this study reveal that brand collaboration and price image exert a positive and significant influence on purchase intention among Passion Jewelry consumers in Jakarta. Based on these findings, it can be concluded that both independent variables, along with the mediating variable, can effectively enhance the purchase intention of Passion Jewelry consumers. A limitation of this study is that the survey was conducted with only one diamond jewelry brand, and the respondents were exclusively consumers of the Passion Jewelry brand residing in Jakarta. The implication of this research is to analyze the interaction between the variables of brand collaboration, price image, and design on purchase intention. This study seeks to understand how brand collaboration can enhance price image, which ultimately influences purchase intention. The results of this research are anticipated to provide valuable insights for marketers and producers in formulating effective brand collaboration strategies and price image settings to increase consumer purchase intention.